Respiratory protection masks: Reflections on the regulation and efficiency of the process in the COVID-19 pandemic (Research, Society and Development, 2021)
The COVID-19 pandemic has brought challenges to health worldwide, especially for countries with weaknesses in public policies, such as Brazil.The scarcity and low quality of masks made available at the beginning of the pandemic symbolized the fragility of the system and regulation, in addition to amplifying the risks to the health professional. Reflect on the regulation and publications related to mask processing and report the results obtained in the articles consulted on the safety and efficiency tests on the reuse of respiration masks allowed during pandemic. Cross-sectional descriptive observational study with secondary data collection, search and analysis of technical standards, legislation, health notes and guidelines. Results. Despite existing health legislation on DM (Medical Devices) and processing, the exceptionality in reuse was not matched to guidelines or rules by Anvisa to ensure efficiency and safety. The articles presented trials for viral inactivation, for filtration efficiency and integrity. There were 37 described essays added to five from a narrative review. Of the 42, 26 confirmed viral inactivation, 15 ensured filtration and 15 ensured post-processing integrity. The reuse of single-use products without specific rules makes Anvisa’s gaze urgent for scientific studies that direct new parameters and the development of new regulations, not only for masks, but for processes that must guarantee products with characteristics similar to that made available by the manufacturer before reuse.